URGENSI HAK ANGKET, PEMAKZULAN PRESIDEN DALAM SISTIM KETATANEGARAAN INDONESIA - Hadi Karyono; Mahmudah Pancawisma; Benny Bambang Irawan (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2024)
In the Indonesian constitutional system, the House of Representatives is given legislative, budgetary and supervisory functions. In carrying out its functions, the House of Representatives is given the right of interpellation, the right of inquiry and the right to express opinions as regulated in the law and other statutory regulations. Impeachment of the President or what is known as the removal of the President in the constitutional system is regulated in the 1945 Constitution of the Republic of Indonesia articles 7A and 7B. In article 7A it is stated that